Combination of mRNA and protein microarray analysis in complex cell profiling - Simara, P; Koutna, I; Stejskal, S; Krontorad, P; Rucka, Z; Peterkova, M; Kozubek, M (Neoplasma, 2009)
UNLABELLED: This study combines mRNA and protein analysis using cDNA and antibody microarray techniques, respectively. These create a novel, integrated perspective into cellular molecular profiles. The aims of this study were to establish a reliable way of integrating these two approaches in order to obtain complex molecular profiles of the cell and to find suitable methods to normalize the data obtained using these approaches. Antibody microarray and cDNA microarray techniques were used to study expression alterations in HL-60 cells that were differentiated into granulocytes using all-trans retinoic acid (ATRA). We selected this model to evaluate this combined profiling technique because the expression levels of most of the mRNA and protein species in these cells are not altered; therefore it is easier to track and define those species that are changed. The proteins whose levels were altered included c-myc, c-jun, Pyk2, FAK, PKC, TRF1, NF-kappaB and certain caspase types. These proteins are involved in apoptosis and hematopoietic differentiation pathways, and some have also been reported to have oncogenic potential. We compared the results obtained using the two methods, verified them by immunoblotting analysis, and devised normalization approaches. This is one of the first demonstrations that a combination of antibody microarray and cDNA microarray techniques is required for complex molecular profiling of cells based on multiple parameters. This approach allows a more detailed molecular phenotype of the given sample to be obtained. The results obtained using a combination of the two profiling methods are consistent with those from previous studies that used more traditional methods. KEYWORDS: microarray, cell profiling, protein expression, mRNA expression, HL-60.
Keywords: Oligonucleotide Array Sequence Analysis; geny myc; Humans; Genes, myc; Telomeric Repeat Binding Protein 1; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; protein TRF1; HL-60 buňky; HL-60 Cells; Protein Array Analysis; čipová analýza proteinů; lidé; Focal Adhesion Kinase 2; RNA, Messenger; tretinoin; Tretinoin; messenger RNA; fokální adhezní kinasa 2